Sonic Hedgehog Initiates Cochlear Hair Cell Regeneration through Downregulation of Retinoblastoma Protein - Lu, Na (2012)
Cell cycle re-entry by cochlear supporting cells and/or hair cells is considered one of the best approaches for restoring hearing loss as a result of hair cell damage. To identify mechanisms that can be modulated to initiate cell cycle re-entry and hair cell regeneration, we studied the effect of activating the sonic hedgehog (Shh) pathway. We show that Shh signaling in postnatal rat cochleae damaged by neomycin leads to renewed proliferation of supporting cells and hair cells. Further, proliferating supporting cells are likely to transdifferentiate into hair cells. Shh treatment leads to inhibition of retinoblastoma protein (pRb) by increasing phosphorylated pRb and reducing retinoblastoma gene transcription. This results in upregulation of cyclins B1, D2, and D3, and CDK1. These results suggest that Shh signaling induces cell cycle re-entry in cochlear sensory epithelium and the production of new hair cells, in part by attenuating pRb function. This study provides an additional route to modulate pRb function with important implications in mammalian hair cell regeneration.